Improving Mammogram Referrals in Hmong Women Utilizing Culturally-aware Patient Education Materials - Wilusz, Sandra (My University, 2018)
Background: Screening mammograms are an important aspect of early detection of breast cancer. The American Cancer Society (2017) recommends that women with average risk of breast cancer start yearly screening mammograms at the age of 40 and continue as long as a woman is in good health. Currently 67% of all United States (U.S.) women participate in routine screening. However, only 30% of Hmong women follow the recommended guidelines. Objectives: The aim of this Doctor of Nursing Practice (DNP) project was to launch a quality improvement (QI) initiative to improve mammogram referrals in Hmong women. Methods: Utilizing the health belief model, culturally-aware mammogram patient education materials were utilized in two primary care offices in Burke County, North Carolina over four months. The materials included Hmong interpreter services, a written translated educational handout and two culturally-aware mammography videos. Results: Prior to the intervention, the organization’s mammogram rate for Hmong women was 57%. After providing culturally-aware mammogram patient educational offerings to 20 Hmong women due for a screening mammogram, 80% percent of the Hmong participants educated by the providers agreed to have a screening mammogram. The culturally-aware videos were found to be more effective than the translated handout in the patient agreeing to have a mammogram. Discussion: This DNP project improved the providers’ knowledge and understanding of Hmong culturally-aware mammogram offerings and the mammogram referral rate for the participants.
Doctor of Nursing Practice Scholary Project
Keywords: Hmong population, Hmong women, Hmong culture, screening mammograms, early detection of breast cancer, barriers to cancer screening, culturally-aware, health disparities, health belief model, health literacy, patient educational programs, interpreters, educational videos, health care beliefs, and Asian women